IMPACT OF CLIMATE ANOMALY ON CATCH COMPOSITION OF NERITIC TUNA IN SUNDA STRAIT - Khairul Amri; Fayakun Satria (Indonesian Fisheries Research Journal, 2013)
Tongkol komo/kawakawa (Euthynnus affinis) and tenggiri (Scomberomerus guttatus) are commonly caught by mini purseiners operated in Sunda Straits and landed in Labuan, West Java. This species inhabits coastal water and has preference staying in relatively warm water. Oceanography parameters commonly influencing the distribution of Euthynnus affinis are temperature, current, and salinity. The oceanography of Sunda Strait is influenced by water masses coming from the north that mainly originated from the Java Sea and water masses from the south mainly originated from Indian Ocean. The internal oceanography of Sunda Strait is also influenced by upwelling and monsoon as regional climate anomaly (ENSO and Indian Ocean Dipole Mode). This paper describes the influence of Dipole Mode (positive and negative event) and ENSO (El- Nino/La-Nina) to the catch dynamics of neritic tuna particularly in Sunda Straits waters. The results shown that regional climate anomaly influenced neritic tuna catch and its composition. The catches Euthynnus affinis in phase negative dipole mode or La-Nina were higher and dominated the catch composition of pelagic fishes of Sunda Strait. Similar situation also is showen by Scomberomorus commerson.